Pengaruh Latihan Mandiri dan Berpasangan terhadap Keterampilan Passing Bawah Permainan Bola Voli Ekstrakulikuler SMP Negeri 01 Bangunrejo - Anggeraini, Vita; Dody Ariesna, Rachmat; Rahmawati, Divya Zuhra (CV. Creative Tugu Pena, 2024)
A form of training that can have an influence on volleyball skills is the use of independent and pair training methods. With the initial attitude, namely standing facing each other, then passing repeatedly and don't let the ball fall and the direction of the ball is unstable. The aim of this research is to find out whether there is an influence on the extracurricular students' under-passing skills in volleyball at SMP Negeri 01 Bangunrejo through independent and pair training methods. The type of this research is quantitative research, this type of research is quantitative research, the experimental method is an activity that includes an initial test, giving exercises, and a final test. Based on the results of the hypothesis test, this research shows that there is a significant influence between independent and pair training on lower passing skills. The results of the T Test calculation, where ????????????????????????? = 2.799 using a significance of 5% and d.b = (N-1) = (24-1) = 23, obtained a value of ???????????????????????? = 0.173. Based on the categories above, there is a value of ????????????????????????? > ???????????????????????? or 2.799 > 0.173. or the increase between the pre-test and post-test was 11.71 or 12.65% with a mean deviation of 0.731. So the null hypothesis (Ho), so the alternative hypothesis (Ha) is accepted. The results of the data analysis above obtained a value of R=0.524, a value of F=2.799 with a significance of p = 0.000 (<0.01), so independent and pair training has an influence on the bottom passing skills of extracurricular students at SMP Negeri 01 Bangunrejo. Keywords: Effects of Independent Practice, Effects of Paired Practice, Volleyball Skills